Sikap Media Dalam Kasus Dugaan Korupsi Gibran-Kaesang - Indah Suryawati; Titi Widaningsih (Avant Garde, 2022)
Reports of alleged corruption cases Gibran-Kaesang to the KPK have attracted the attention of online media. Kompas.com and Wartaekonomi.co.id are news portals that consider this important issue. The purpose of this study is to explain Kompas.com and Wartaekonomi, co.id attitude in reporting the Gibran-Kaesang corruption alleged report and to uncover the form of domination in the news. The method used is Robert N. Entman framing model. The paradigm used is the constructive paradigm. The object of research is the reporting of alleged corruption by Gibran-Kaesang on Kompas.com and Wartaekonomi.co.id during the period from January 10, 2022 to January 21, 2022. The results show that Kompas.com and Wartaekonomi.co.id construction is presented differently. Kompas.com constructs this reality from the political aspect, while Wartaekonomi.co.id from the political and legal aspects. Kompas.com tends to be neutral. Unlike the case with Wartaekonomi.co.id, which is more daring to be against it. Kompas.com does not highlight certain images in its reporting. In fact, Wartaekonomi.co.id highlighted Ubedillah's positive image and created a negative image of Gibran. Wartaekonomi.co.id seems to position its news portal as an alternative media that forms an alternative public space, namely a room for protest and critical politics, even though it is not maximized.